2022
DOI: 10.3390/d14040259
|View full text |Cite
|
Sign up to set email alerts
|

Turnover Drives High Benthic Macroinvertebrates’ Beta Diversity in a Tropical Karstic Lake District

Abstract: Beta diversity is useful to explain community assembly across landscapes with spatial variation. Its turnover and nestedness components help explain how beta diversity is structured across environmental and spatial gradients. Assessing beta diversity in freshwater ecosystems is essential to conservation, as it reveals the mechanisms that maintain regional diversity. Nonetheless, so far, no studies have examined the beta diversity patterns of benthic macroinvertebrates in tropical lakes. We aimed to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Most copepods belong to the genera Mastigodiaptomus, Leptodiaptomus, Mesocyclops, and Thermocyclops, all with greater diversity in tropical areas [28,58,59]. Recently, [12] explained that the closeness between lakes and the high environmental heterogeneity promoted species turnover, resulting in the large regional diversity but great singularity level among the benthic macroinvertebrates of the "Lagunas de Montebello" National Park lakes. The same large regional diversity but great singularity in these lakes have been reported for the zooplankton and benthic macroinvertebrates communities [10,11,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most copepods belong to the genera Mastigodiaptomus, Leptodiaptomus, Mesocyclops, and Thermocyclops, all with greater diversity in tropical areas [28,58,59]. Recently, [12] explained that the closeness between lakes and the high environmental heterogeneity promoted species turnover, resulting in the large regional diversity but great singularity level among the benthic macroinvertebrates of the "Lagunas de Montebello" National Park lakes. The same large regional diversity but great singularity in these lakes have been reported for the zooplankton and benthic macroinvertebrates communities [10,11,60].…”
Section: Discussionmentioning
confidence: 99%
“…This unicity justifies its designation as a natural protected area by presidential decree in 1959, RAMSAR Site in 2003, and Biosphere Reserve MAB-UNESCO in 2009. Previous studies [10,11] suggested a great regional (i.e., the whole lake district) aquatic biodiversity but a large individual singularity (i.e., very few taxa present in more than a lake), stressing the fragility of these aquatic ecosystems [12]. Belonging to the same lake district and located close to each other, sharing the same climate, and with similar physical and chemical characteristics, it is unusual that these lakes share a small number of common species of the few biological communities investigated so far (rotifers, benthic macroinvertebrates).…”
Section: Introductionmentioning
confidence: 99%